Peningkatan Pemahaman Konsep Pengukuran Panjang Pada Anak Usia 5-6 Tahun Melalui Kegiatan Fun Cooking Di TK Az-Zahra Kabupaten Lahat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Understanding the concept of length measurement is an essential part of early childhood cognitive development, particularly in introducing basic mathematical skills such as comparing and ordering objects by size. Initial observations at TK Az-Zahra, Lahat Regency, showed that 73.3% of children aged 5–6 years had difficulty distinguishing between long and short, as well as ordering objects according to size. This indicates a gap between the expected competencies stated in the Early Childhood Development Achievement Standards (STTPA) and the children’s actual performance. This study aims to improve children’s understanding of length measurement concepts through fun cooking activities. The research employed a Classroom Action Research (CAR) design using the Kemmis and McTaggart model, consisting of four stages: planning, action, observation, and reflection. The results showed an improvement in the children’s understanding of length measurement, with the average achievement increasing from 53,75% in the pre-cycle to 68,5% in cycle I, and reaching 81,83% in cycle II. These findings indicate that the implementation of fun cooking activities in an active and enjoyable manner plays a positive role in helping children understand the concept of length measurement in a concrete and meaningful way